Type 1b Endoleaks After Thoracic Endovascular Aortic Repair are Inadequately Reported: A Systematic Review - Belvroy, Viony M.; de Beaufort, Hector W.L.; van Herwaarden, Joost A.; Trimarchi, Santi; Moll, Frans L.; Bismuth, Jean (Annals of vascular surgery, 2020)
Complications after thoracic endovascular aortic repair (TEVAR) are common. Even after a successful TEVAR, a late endoleak (>30 days) can occur. The objective of this study is to summarize the current evidence and, if lacking, the need of evidence regarding the incidence and predictive factors for type 1b endoleak in patients with aortic aneurysm treated with TEVAR. A systematic review of the literature was performed on endoleak type 1b, in patients with aortic aneurysm, after TEVAR. The PubMed and Embase databases were systematically searched for articles regarding endoleak type 1b up to January 2019. The main subjects discussed are the incidence, risk factors, treatment, and prognosis. About 722 articles were screened, and 16 articles were included in this review. The reported incidence of endoleak is between 1.0% and 15.0%, with a mean follow-up duration of at least 1 year. Type 1b endoleak is associated with an increased aortic tortuosity index (>0.15 cm−1). No significant difference is found in relation to age and gender. Treatment is required in most cases (22/27) and is usually performed with distal extension of the stent graft (21/27). There are no data regarding stent graft oversizing, length of distal landing zone, and differences between devices or the prognosis for patients with type 1b endoleak. Limited literature is available on the occurrence of type 1b endoleak after TEVAR. A tortuous aorta can be associated as a predictive factor for the occurrence of type 1b endoleak. Data clearly delineating the anatomic variables predicting type 1b endoleak should be examined and listed. Likewise, the impact of more recent conformable devices to prevent complications like type 1b endoleaks from occurring should be elucidated.